Effective Approaches to Energy Planning and Classification of Energy Systems Models - Mougouei, Farzad Rahimi; Mortazavi, Mahdieh-Sadat (International Journal of Energy Economics and Policy, 2017)
A balance between energy supply and demand is one of the challenges faced by policy makers. In fact, the main objective of energy planning is to achieve this balance. Energy models can be used for supply and demand future planning of a country or region. In most situations, these methods focus on economic development, energy policy, selection of appropriate resources and technologies for the future and investing in these technologies. This paper discusses the definitions of energy planning and classifies models of energy systems according to various approaches. The paper concludes that overall energy planning requires a balance between supply and demand of energy. However, achieving this balance is possible with the coordination of all energy sectors, proper development and implementation of energy policies and finally guidance and help to the consumer to select the best sources. Keywords: Energy planning, Energy systems modeling, Energy management JEL Classifications: O13, Q4